Բառի սահմանումն ըստ էդուարդ Աղայանի - Իրինա Մովսիսյան (Տաթև գիտակրթական համալիր, ՀՀ ԳԱԱ Հ. Աճառյանի անվան լեզվի ինստիտուտ)
В лингвистике теория слова и его дефиниция являются стержневыми. Многие лингвисты пытались дать определение слову, но до сих пор не сошлись в едином мнении. В армянском языкознании о слове и его теории наиболее подробно писал академик Эд. Агаян. В статье исследуются предложенные Эд. Агаяном важнейшие признаки описания слова и определение, сделанное на их основе. Это определение не совершенно, но, т.к. распространяется на подавляющее большинство слов, является лучшим из данных по сей день определений. In linguistics the theory and definition of the word occupies a pivotal place. Many attempts have been made by different linguists to define the word, but so far unanimous conclusion has been achieved. In Armenian linguistics the details of the theory of the word have been thoroughly discussed by academician Edward Aghayan. The present paper deals with the analysis of various properties of the word discussed and defined by Ed. Aghayan. The research shows that although the definition of the word put forward by Ed. Aghayan can never be viewed as perfect for all possible lexical units, it is adequate for the majority of words. Thus, the theory of the word elaborated by academican Ed. Aghayan is considered to be the most appropriate one.
Keywords: Լեզու և գրականություն; Լեզվաբանություն